2022
DOI: 10.1177/17411432221113912
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how power distance influences principal instructional leadership effects on teacher agency and classroom instruction in Oman: A moderated-mediation analysis

Abstract: Nations throughout the world have been engaged in efforts to redefine the role of principals to include instructional leadership. This is based upon research that has verified a positive indirect relationship between principal instructional leadership and student learning. This study tested a moderated mediation model of how the power distance orientation of teachers influences the effects of principal instructional leadership on teacher agency and classroom instruction. Data collected from 464 teachers in 65 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 61 publications
(222 reference statements)
1
6
0
Order By: Relevance
“…These findings support the assumption that in today's schools, it is unrealistic to expect that principals have enough knowledge and time to directly engage in instructional work with teachers (Grissom et al, 2013;Liebowitz and Porter, 2019). The previously mentioned empirical findings contributed to the generation of a wave of studies on the indirect effects of school leadership on teaching practice (Hendawy Al-Mahdy et al, 2022). The new stream of research, which is gaining momentum, focuses on classroom instruction rather than student achievement as an outcome variable.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…These findings support the assumption that in today's schools, it is unrealistic to expect that principals have enough knowledge and time to directly engage in instructional work with teachers (Grissom et al, 2013;Liebowitz and Porter, 2019). The previously mentioned empirical findings contributed to the generation of a wave of studies on the indirect effects of school leadership on teaching practice (Hendawy Al-Mahdy et al, 2022). The new stream of research, which is gaining momentum, focuses on classroom instruction rather than student achievement as an outcome variable.…”
Section: Introductionsupporting
confidence: 63%
“…Two studies have simultaneously examined moderating and mediating relationships between constructs. Hendawy Al-Mahdy et al (2022) found that instructional leadership is directly and indirectly, via teacher agency, related to teacher work. The effect of school leadership on the mediator variable, teacher agency, was greater when the power distance in principal-teacher relations was less pronounced.…”
Section: Indirect Effects Of School Leadership On Instructional Quali...mentioning
confidence: 99%
“…Nevertheless, research insights from cross-sectional studies are acceptable in educational administration research and are considered informative when keeping this limitation in mind (e.g. Bellibaş et al ., 2021; Hendawy Al-Mahdy et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Second, although the knowledge base on the association between leadership and teaching is well established in Western nations (Heck and Hallinger, 2014), empirical studies have only recently begun to emerge in Asia (Hendawy Al-Mahdy et al ., 2022) or other non-English speaking regions (Pietsch and Tulowitzki, 2017). Therefore, a higher density of further research from different educational settings might advance our understanding of the link between leadership and teaching.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, following Liebowitz and Porter (2019, p. 793), who suggested that "future research should focus more on specific leadership practices rather than overarching styles or models," we measured school leadership as a set of practices including setting direction, building relationships and developing people, developing the organization to support desired practices and improving the instructional program (Leithwood, 2012). Second, although the knowledge base on the association between leadership and teaching is well established in Western nations (Heck and Hallinger, 2014), empirical studies have only recently begun to emerge in Asia (Hendawy Al-Mahdy et al, 2022) or other non-English speaking regions (Pietsch and Tulowitzki, 2017). Therefore, a higher density of further research from different educational settings might advance our understanding of the link between leadership and teaching.…”
mentioning
confidence: 99%